2021
DOI: 10.3390/molecules26041099
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect and Cytotoxic Evaluation of Mg-Doped Hydroxyapatite Functionalized with Au-Nano Rods

Abstract: Hydroxyapatite (HA) is the main inorganic mineral that constitutes bone matrix and represents the most used biomaterial for bone regeneration. Over the years, it has been demonstrated that HA exhibits good biocompatibility, osteoconductivity, and osteoinductivity both in vitro and in vivo, and can be prepared by synthetic and natural sources via easy fabrication strategies. However, its low antibacterial property and its fragile nature restricts its usage for bone graft applications. In this study we functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Calabrese et al reported a synthesis of HA-Col porous scaffolds [ 60 , 131 , 132 ] reinforced with silver and gold nanoparticles [ 131 , 133 ], satisfying both antimicrobial and osteo-regenerative properties [ 134 ]. The scaffolds were prepared by incorporating Col with bioactive magnesium-doped nHA and stabilizing the structure with the highly reactive BDDGE.…”
Section: Crosslinking Methods and Agents In Ha-based Composite Scaffoldsmentioning
confidence: 99%
“…Calabrese et al reported a synthesis of HA-Col porous scaffolds [ 60 , 131 , 132 ] reinforced with silver and gold nanoparticles [ 131 , 133 ], satisfying both antimicrobial and osteo-regenerative properties [ 134 ]. The scaffolds were prepared by incorporating Col with bioactive magnesium-doped nHA and stabilizing the structure with the highly reactive BDDGE.…”
Section: Crosslinking Methods and Agents In Ha-based Composite Scaffoldsmentioning
confidence: 99%
“…The release of metal ions (positively charged) to the surface of bacteria (negatively charged) enhances antimicrobial activity by destabilization of cell membrane and, inside cells, by proteins denaturation (especially ribosome proteins) [25]. However, often antibacterial effects are associated to cytotoxicity with a consequent increase of health risk [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically to the biomedical field, CDs gained a growing interest due to their excellent photoluminescence properties, diverse surface functions, good water solubility, low cytotoxicity, cellular uptake, biocompatibility, microbial adhesion, and theranostic properties [ 29 , 30 ]. Among these properties, antibacterial activity is one of the most appealing features in the design of new biomaterials in which nanotechnology is making fundamental contributions [ 31 , 32 , 33 , 34 ]. In this context, the specific physicochemical properties of CDs (e.g., size and surface charge) make them promising tools for addressing antibacterial processes, such as drug resistance, biofilms, and intracellular active/latent bacteria [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%